Diseño de una estrategia de comunicación pública de laciencia sobre patrimonio cultural y arte local en el centrode la provincia de Buenos Aires (Argentina) - Giacomasso, María Vanesa (2024)
The communication of cultural heritage studies does not always constitute a central action of research projects. Therefore, the objective of this work is to present the design of a public science communication strategy on cultural heritage and local art in the district of Olavarría (Argentina). The proposal arises from the making of a documentary and its low visibility and exchange with the public. To achieve this, methodologically it is proposed to work from communication planning based on contextual models and citizen participation. The main result is the development of a communication strategy, based on transmedia formats and focused on the local educational sector. It concludes on the importance of articulating cultural heritage research with social sectors that are susceptible to becoming aware of their environment and that have a high potential to get involved in its protection and safeguarding.